Analisis Perkembangan Perilaku Dan Emosional ABK Hiperaktif Yang Mengalami Gangguan Konsentrasi Di Sekolah Ra Al-Hidayah - Ageng Saepudin Kanda S; Risda Laila Purnama (Student Scientific Creativity Journal, 2024)
The behavioral and emotional development of hyperactive children causes children to experience problems concentrating in learning, because the disorders they experience cannot be controlled properly. Therefore, children experience difficulties when learning takes place and this has an impact on social relationships which influence their behavior when interacting with other people or their peers. So the researcher raised the problem in his research, namely the behavioral and emotional development of hyperactive children with special needs who experienced concentration problems in learning at the Raudhatul Athfal Al-Hidayah school. This research aims to determine developmental aspects of children's behavior and emotions as well as indicators related to hyperactivity and disturbances in concentration. This research uses a descriptive qualitative research method by collecting data through a process of observation, interviews and documentation. The results of this research show that the behavioral and emotional development of hyperactive children is all excessive behavior and actions seen when children express their emotions when they are happy, sad, angry, disappointed, anxious and afraid. Children's emotional development impacts children's behavior, such as being aggressive, running around, shouting, being rude, talking a lot, being nosy and endangering people around them. This can happen because there are many factors that underlie a child becoming a hyperactive child, namely genetics, slow development of the child's brain, parenting patterns, emotional intelligence and the influence of the surrounding environment.